The Role of Youth Organizations in Community Empowerment through Screen Printing Business in Krembung Village, Krembung District, Sidoarjo - Tusya'diyah, Halimah; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to describe and analyze the role of youth organization in community empowerment in Krembung Villange, Krembung District, Sidoarjo Regency. The type of research used is descriptive qualitative research. Data collection techniques are carried out through observation, interviews, and documentations. Determination on informants in this study using purposive sampling technique. Data analysis technique using Miles & Huberman theory namely data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the empowerment of villange communities through youth organizations is seen from three indicators of the role of youth organizations, namely as a motivator for the role of youth organizations by holding entrepreneurship socialization by inviting the Krembung Villange community. As a facilitator of the role of the Krembung villange youth organization, conducting training on screenings to provide understanding and knowledge of printing techniques by inviting the community to practice it direvtly. While as a mobilizer for the role of youth organizations is this case mobilizing or directing people who are already running a soap business to develop more. In developing this business, youth organizations held a bazaar exhibitions through the youth organization instagram